Моделі оцінки діяльності авіадиспетчерів в реагуванні на проблемні ситуації на диспетчерських тренажерах - Григорецький, Володимир Олексійович; Неділько, В. М.; Пальоний, А. С. (НТУ "ХПІ", 2015)
Розглянуто принципи побудови моделей оцінки дій авіадиспетчерів, що базуються на причинно-наслідковій моделі ризику для повітряного транспорту. Подано класифікацію типових помилок та приклади застосування дерев помилок авіадиспетчерів за критеріями безпомилковості і своєчасності реагування на проблемні (конфліктні) ситуації.

The principles of construction evaluation models the air traffic actions of controllers based on a causal model of risk for air transport. The classification of typical mistakes and errors examples of the application of the trees the air traffic controllers on the criteria of correctness and timeliness of response to the problem (conflict) situation.
Assessment models of air traffic controller performance in response to problem situation used in simulator
Keywords: дії авіадиспетчерів; причинно-наслідкова модель; повітряний транспорт; ризик; air traffic controller; model for evaluating actions of air traffic controllers; causal risk model; air transport; trainer